Association Between Breast Arterial Calcifications Found on Mammography and Increased Risk of Coronary Artery Calcifications in Asian Populations: A Literature Review - Aulia Wiratama Putra; Tasya Khalis Ilmiani; Dinda Ariesta; Evan Nugroho; Bagas Wahyu Utama; Ayers Gilberth Ivano Kalaij (GLOBAL HEALTH SCIENCE GROUP, 2026)
Mammography examination of the breast has been widely used throughout the world, but many findings found through this modality have been overlooked, one of which is breast arterial calcification (BAC). Breast cancer is often experienced by millions of women in the world, signs are usually screened for breast cancer using mammography. This literature review aims to assess the association between BAC found on mammography and increased risk of coronary artery calcifications in Asian populations. An initial search was carried out using reference sources from the electronic databases PubMed, Scopus, Cochrane, Wiley, ScienceDirect, EBSCOhost, and Google Scholar, using keywords